(3JgPjH GdhUhd aj Yde GdCUhds - (3GdMdj, CHh efUhQ, GHf GdeWgQ, LeGd GdOjf, GdMSf Hf jhSa Hf Ydj GHf GdeWgQ, J (B726(3g`s
(3ChdgG (B:s
(3GdMeO ddg (B... (3MQQJ ajg WQa GdCMcGe Ydi GdELeGd ef ZjQ JWhjd hdG ENdGd ELGHI dGdJeGS hdOj eMeO (B.. (3hQJHJ gPG GdcJGH Ydi ebGUO GdebUO GdChd aj GdebOeGJ hajg aUhd , GdChd aj eHGMK egeI JUhQ GdeQcH (B...s
(3BNQgG (B:s
... (3GdbSe GdKGfj NdGa Pdc GdNHQ dG jYQa EdG HGdYde dGf YOG GdYde dG jYde EdG efg adh cGf eYQaG ddYde ddYde cGf cdeI hGMOI efgeG eYQaG dUGMHg (B...(3hPdc HdRhe dchf cd efgeG CYQa hCLdi (B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe , ddRQcdj (B2/227s
(3EjVGM Gdecfhf (B1\342s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs